KETERPADUAN GAGASAN PADA TEKS WACANA NARATIF (Analisis Teks Wacana Naratif Berbahasa Mandarin) - Subandi, Subandi; Damayanti, Dhilla Astari; Masrur, Muhammad Farhan; Arista, Cicik; Bagus Adimas, Yogi (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2022)
Cohesion and coherence have a very significant role in the formation of an integrated structure and an integrated meaning of the text of discourse. The accuracy of the use of lingual units as a marker of the type of cohesion and coherence is an absolute demand in forming a good text structure. This study examines how cohesion and coherence forms in the Chinese narrative texts compiled by students. The results of the research are presented in narrative form to provide a concrete, comprehensive and as-is-what explanation according to the focus of the problem. The research data is in the form of the types of cohesion and coherence in the students' Mandarin-language narrative texts. There are as many as 35 discourse texts which are then taken 10 discourse texts as samples using purposive sampling as research objects. Data collection techniques used document analysis techniques, namely, a way of collecting data by analyzing the contents of documents related to the problem under study, then presenting the results descriptively. From the data analysis, the following results were obtained. (1) Cohesion in Chinese discourse texts compiled by students is in grammatical and lexical form. Cohesion in the form of reference elements is dominated by lingual units in the form of personal pronouns I. Conjugation elements dominate grammatical cohesion and repetition elements dominate lexical cohesion. (2) Coherence in the Chinese language discourse text compiled by students, there are types of relationships, namely, causal relationships and conflicting relationships. The type of cause-and-effect relationship is more dominant than the type of conflicting relationship. Keywords: Cohesion, Coherence, Discourse Text, Narrative